DAMPAK ASURANSI KESEHATAN TERHADAP PEKERJA ANAK DI INDONESIA: PROPENSITY SCORE MATCHING - Ratih Ramadhani; Hesty Aisyah (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study examines the effect of household health insurance ownership, particularly the BPJS Penerima Bantuan Iuran (PBI) scheme, on the likelihood of children from poor families engaging in work. In vulnerable households, children are often pushed into the labor market when parents fall ill and lose income. Using data from the 2022 National Socioeconomic Survey (SUSENAS) and the Propensity Score Matching (PSM) method, this research compares the probability of child labor between poor households with and without BPJS PBI coverage. The results indicate that health insurance ownership has not been effective in reducing child labor risk. Children from insured households are found to be 0.96 percentage points more likely to work than those from uninsured households. This suggests a reverse causality effect, where economically vulnerable families with higher health risks are more likely to enroll in BPJS PBI but still rely on children’s labor due to persistent financial pressures. The study concludes that health insurance programs should be complemented by broader social protection policies, such as conditional cash transfers, education scholarships, and household economic empowerment programs, to more effectively protect children from labor and break the intergenerational cycle of poverty.